EXPLORING THE BANKERS’ PERSPECTIVES ON SHARIAH AND OPERATIONAL ISSUES OF RESTRUCTURING AND RESCHEDULING IN ISLAMIC FINANCING DURING COVID-19 PANDEMIC (International Journal of Islamic Business, 2023)
The Central Bank of Malaysia ordered all banks to give an automatic six months moratorium or loan or financing deferment starting April, 1 2020 to their customers during the Covid-19 pandemic since many customers had difficulties paying their monthly financing obligations to banks. Thus, the objective of this paper is to explore the bankers’ perspectives on Shariah and operational issues arising in Islamic banks in implementing moratorium which involves restructuring and rescheduling financing facilities during Covid-19 pandemic. At the same time, the methods these bankers used to manage the issues are also highlighted in this paper. A qualitative analysis is applied in this paper where the researchers conducted interview sessions with the Head of Shariah Department from an Islamic banking window and another from the Development Financial Institution which offers Islamic banking products and services. This study's findings show that there are certain perspectives from bankers in dealing with Shariah issues regarding restructuring and rescheduling during moratorium such as the issue of qalb al-dayn (debt restructuring), capitalization of accrued profit in the financing facilities as well as the operational issues related to the system and people. It can be deduced then that all Islamic banks were doing extremely well in their steadfast endeavors towards offering remedies to the issues faced for the sake of the overall improvement of Islamic banks in the implementation of restructuring and rescheduling of financing facilities as outlined by guidelines or Resolutions issued by the Shariah Advisory Council of Bank Negara Malaysia.